Jagode u grlu . A Throat Full of Strawberries (aka Caught In The Throat, Strawberries in the Throat) - Karanović, Srđan (Avala Pro-Film Beograd, 1985)
Director Srđan Karanović, a member of the so-called Prague school, returned once again to the characters he created for his legendary TV series and brought their lives up-to-date in this sequel which happens 15 years after the end of the final episode. Although fully understood only in the context of the whole series, a film functions equally well as a separate full-feature unit. The film begins with a sentimental meeting of the old friends who gather on a boat-restaurant where Bane Bumbar, his wife Biljka, and friends Goca, Uške and Boca celebrate the arrival of their friend Miki from abroad. Immediately, they start to remember their youth from the sixties, as well as recapitulating their past lives and boasting of new achievements, each trying to outdo the others. A peaceful reunion soon develops into a night of fierce discussions and the film quickly acquires the dark and depressiing tones of the last episodes of the series since it is obvious that most of their lives did not go the way they planned.